Pleomorphic xanthoastrocytoma with NTRK fusion presenting as spontaneous intracranial hemorrhage—case report and literature review - Wu, Yilong; Aw, Sze Jet; Jain, Swati; Ooi, Li Yin; Tan, Enrica E. K.; Chang, Kenneth T. E.; Teo, Harvey J.; Seow, Wan Tew; Low, Sharon Y. Y. (Frontiers in Pediatrics, 2024)
Pleomorphic xanthoastrocytoma (PXA) is a rare brain tumor that accounts for less than 1% of all gliomas. In-depth understanding of PXA's molecular makeup is still a work in progress owing to its limited numbers globally. Separately, spontaneous intracranial hemorrhage (pICH) is an uncommon but potentially devastating emergency in young children. Usual causes include vascular malformations or underlying haematological condition. The authors describe an interesting case of a toddler who presented with pICH that was found to have a PXA as its underlying cause of hemorrhage. Further molecular interrogation of the tumor revealed a neurotrophic tyrosine receptor kinase (NTRK) gene fusion and CDKN2A deletion more commonly seen in infantile high-grade gliomas. The unusual clinicopathological features of this case are discussed in corroboration with published literature.A previously well 2-year-old male presented with acute drowsiness and symptoms of raised intracranial pressure secondary to a large right fronto-parietal intracerebral hematoma. He underwent an emergency craniotomy and partial evacuation of the hematoma for life-saving measures. Follow-up neuroimaging reported a likely right intra-axial tumor with hemorrhagic components. Histology confirmed the tumor to be a PXA (WHO II). Additional molecular investigations showed neurotrophic tyrosine receptor kinase (NTRK) gene fusion and CDKN2A deletion. In view of the more aggressive intra-tumoral features, a consensus by a multi-disciplinary team was for second stage surgical removal of the remnant tumor, followed by adjuvant chemotherapy.To date, there are very few pediatric cases of PXA that present with spontaneous pICH and whose tumors has undergone thorough molecular testing. Our patient's journey highlights the role of a dedicated multi-disciplinary neuro-oncology team to guide optimal treatment.